MANAGEMENT OF SEMI-WILD LARGE HERBIVORES’ GRAZING SITES IN LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Large herbivores were a common part of European nature in the pre-agrarian times. With the development of farming and over-hunting, the number of wild large herbivores rapidly decreased. Wild horses and cattle became extinct. In the 1920-30’s, scientists created two new herbivore breeds that resembled the extinct aurochs and tarpans - Heck cattle and Konik horses. Nowadays the introduction of Heck cattle, Konik horses and other similar large herbivore breeds is widely used in specially protected nature territories (SPNT) as a strategic answer to the question – what should we do with the agricultural lands that have lost their economical meaning. Since 1999, semi-wild large herbivores are introduced in various SPNT of Latvia as well, mainly in nature parks and nature reserves. Based on field visits, interviews and policy analysis, this paper discusses two main approaches to semi-wild grazing animal population management in Latvia: (1) introduced herbivores as a part of rewilding process and (2) introduced herbivores as instruments for habitat protection. The former represents the implementation of western wilderness values, while the latter is related to more specific protection of species and habitats according to particular place-based nature protection goals. This study contributes to the growing discussion on rewilding practises in Europe and the introduction ideas of semi-wild animals, as well as landscape management practices in the era of post-productivism.